Textbook of Catheter-Based Cardiovascular Interventions A Knowledge-Based Approach (Springer International Publishing, 2018)
This book is a fully updated and revised second edition of a highly successful text in which a new concept of knowledge mining, based on explication and transfer of interventional knowledge of experts, has been implemented. The dedicated training program that is set out will serve the needs of all interventional operators, whether cardiologists, vascular surgeons, vascular specialists, or radiologists, enabling them to achieve a consistent expert level across the entire broad spectrum of catheter-based interventions. Operator skills - and in particular decision-making and strategic skills - are the most critical factors for the outcome of catheter-based cardiovascular interventions. Currently, such skills are commonly developed by the empirical trial and error method only. The explicit teaching, training, and learning approach adopted in this book permits the rapid transfer of interventional knowledge and enables individual operators to negotiate steep learning curves and acquire complex skills in a highly efficient manner. It will thereby offer invaluable assistance in meeting successfully the challenges of modern cardiovascular care.